Midlatitude Continental CAPE Is Predictable From Large‐Scale Environmental Parameters. Issue 8 (17th April 2021) - Li, Funing; Chavas, Daniel R.
Abstract: A recent study by Agard and Emanuel (2017, https://doi.org/10.1175/jas-d-16-0352.1 ) proposed a simple equation for a quantity that scales with convective available potential energy (CAPE) that can be directly calculated from a limited number of environmental sounding parameters without lifting a hypothetical air parcel. This scaling CAPE was applied in a specific idealized framework, but the extent to which it can predict true CAPE in the real world has not been tested. This work uses reanalysis data over the U.S. to demonstrate that this scaling CAPE does indeed scale very closely with CAPE, following a linear relationship with a scaling factor of 0.44. We then explain why they scale together via a step‐by‐step derivation of the theoretical assumptions linking scaling CAPE and real CAPE and their manifestation in the historical data. Overall, this work demonstrates that CAPE can be predicted from large‐scale environmental parameters alone, which may be useful for a wide range of applications in weather and climate. Plain Language Summary: Convective available potential energy (CAPE) is a key parameter commonly used to measure the potential for thunderstorms. Its calculation requires lifting a hypothetical air parcel through a column of atmosphere. This work combines theory and reanalysis data to demonstrate that CAPE can be predicted using environmental data alone. This can make it easier to quickly estimate CAPE in data and to understand the processes that create CAPE in our atmosphere. Key Points: Convective available potential energy (CAPE) can be predicted from environmental sounding parameters without lifting a hypothetical air parcel A step‐by‐step derivation demonstrates how CAPE scales with a recently proposed CAPE‐like quantity A simple predictive linear equation is presented based on 20 years of reanalysis data over the U.S.